Analisis Pengaruh Harga, Kualitas Produk Dan KualitasLayanan Terhadap Kepuasan Pelanggan Pada RumahMakan Padang Singgalang Indah Surakarta - Winardi, Eka Yulian Rahmat, Dr. Edi Purwo Saputro, SE., M.Si (2016)
Customer satisfaction can be influenced by many factors, including price, product quality and service quality. The object of this study was home eating desert Singgalang Indah Surakarta. The purpose of this study was to determine the effect of price, product quality and service quality to customer satisfaction at home eating desert Singgalang Indah Surakarta. The study population in this study is a community Surakarta who've been in the restaurant field Singgalang Indah.Sampel in this study was 75 respondents. The method of collecting data using questionnaires. Data were analyzed using multiple linear regression. Variable pricing and service quality effect on customer satisfaction, while the variable quality of the product has no effect on customer satisfaction. The independent variables consisting of price, product quality and service quality together (simultaneously) significantly affects customer satisfaction variables. 22.7% variable customer satisfaction can be explained by the variable price, product quality and service quality. ix Thus we recommend businesses should pay attention to the price and quality of service in order to dominate the market.